Four misconceptions about investigative genetic genealogy. Issue 1 (13th April 2021) - Guerrini, Christi J; Wickenheiser, Ray A; Bettinger, Blaine; McGuire, Amy L; Fullerton, Stephanie M
Abstract: Investigative genetic genealogy (IGG) is a new technique for identifying criminal suspects that has sparked controversy. The technique involves uploading a crime scene DNA profile to one or more genetic genealogy databases with the intention of identifying a criminal offender's genetic relatives and, eventually, locating the offender within the family tree. IGG was used to identify the Golden State Killer in 2018 and it is now being used in connection with hundreds of cases in the USA. Yet, as more law enforcement agencies conduct IGG, the privacy implications of the technique have come under scrutiny. While these issues deserve careful attention, we are concerned that their discussion is, at times, based on misunderstandings related to how IGG is used in criminal investigations and how IGG departs from traditional investigative techniques. Here, we aim to clarify and sharpen the public debate by addressing four misconceptions about IGG. We begin with a detailed description of IGG as it is currently practiced: what it is and—just as important—what it is not. We then examine misunderstood or not widely known aspects of IGG that are potentially confusing efforts to have constructive discussions about its future. We conclude with recommendations intended to support the productivity of those discussions.